Suppression of Th1-Mediated Keratoconjunctivitis Sicca by Lifitegrast - Guimaraes de Souza, Rodrigo (J Ocul Pharmacol Ther, 2018)
Purpose: Increased interferon gamma (IFN-γ) expression in dry eye causes ocular surface epithelial disease termed keratoconjunctivitis sicca (KCS). The purpose of this study was to investigated the effects of the LFA-1 antagonist, lifitegrast, in a mouse desiccating stress (DS) dry eye model that develops KCS similar to Sjögren syndrome. Methods: Mice were treated with vehicle or lifitegrast twice daily for 5 days and expression of Th1 family genes (IFN-γ, CXCL9, and CXCL11) was evaluated by real-time polymerase chain reaction. Cornea barrier function was assessed by Oregon Green dextran staining and goblet cell number and area were measured. Results: Compared to the vehicle-treated group, the lifitegrast-treated group had significantly lower expression of Th1 family genes, less corneal barrier disruption, and greater conjunctival goblet cell density/area. Conclusions: These findings indicate that lifitegrast inhibits DS-induced IFN-γ expression and KCS. This suggests that ICAM–LFA-1 signaling is involved with generation of Th1 inflammation in KCS.